Polypoidal choroidal vasculopathy with an exceptionally elevated pigment epithelial detachment - Yanliang Li; Hesham Gabr; William F. Mieler (American Journal of Ophthalmology Case Reports)
Purpose: To present a distinctive case of polypoidal choroidal vasculopathy (PCV) with an exceptionally elevated pigment epithelial detachment (PED). Observations: We describe the case of a 48-year-old African-American woman who presented with a substantial lesion in the right eye. Fundus examination revealed an exceptionally elevated lesion extending in the inter-papilla-macular region with multiple dark pigmented spots. Indocyanine Green Angiography (ICGA) in the early phase displayed focal hyperfluorescent spots and a blockage of fluorescence within the lesion, particularly overlying the papillomacular bundle. In the late phase, hyperfluorescent spots within the lesion became evident, with a hyperfluorescent outline of the lesion indicating vascularization. Optical coherence tomography in the right eye disclosed an exceptionally elevated PED temporal to the optic nerve with an elevation of more than 2500 μm, along with subretinal fluid and trace intraretinal fluid. Conclusions and importance: Multimodal imaging unveiled an atypical case of PCV featuring an exceptionally extensive polypoidal lesion overlying the papillomacular bundle with choroidal neovascularization. Given the presence of a highly conspicuous, elevated PED, it was felt that the risk of retinal pigment epithelium tear was high either with anti-VEGF therapy or even due to natural history. In this scenario, the initial treatment choice was photodynamic therapy rather than intravitreal anti-VEGF injection, which led to complete regression with excellent visual acuity.